Adaptation of the By-Band randomized clinical trial to By-Band-Sleeve to include a new intervention and maintain relevance of the study to practice. Issue 9 (13th July 2017) - Rogers, C A; Reeves, B C; Byrne, J; Donovan, J L; Mazza, G; Paramasivan, S; Andrews, R C; Wordsworth, S; Thompson, J; Blazeby, J M; Welbourn, R; ,
Abstract: Background: Recruitment into surgical RCTs can be threatened if new interventions available outside the trial compete with those being evaluated. Adapting the trial to include the new intervention may overcome this issue, yet this is not often done in surgery. This paper describes the challenges, rationale and methods for adapting an RCT to include a new intervention. Methods: The By-Band study was designed in the UK in 2009–2010 to compare the effectiveness of laparoscopic adjustable gastric band and Roux-en-Y gastric bypass for severe obesity. It contained a pilot phase to establish whether recruitment was possible, and the grant proposal specified that an adaptation to include sleeve gastrectomy would be considered if practice changed and recruitment was successful. Information on changing obesity surgery practice, updated evidence and expert opinion about trial design were used to inform the adaptation. Results: The pilot phase recruited over 13 months in 2013–2014 and randomized 80 patients (79 anticipated). During this time, major changes in obesity practice in the UK were observed, with gastric band reducing from 32·6 to 15·8 per cent and sleeve gastrectomy increasing from 9·0 to 28·1 per cent. The evidence base had not changed markedly. The British Obesity and Metabolic Surgery Society and study oversight committees supported an adaptation to include sleeve gastrectomy, and a proposal to do so was approved by the funder. Conclusion: Adaptation of a two-group surgical RCT can allow evaluation of a third procedure and maintain relevance of the RCT to practice. It also optimizes the use of existing trial infrastructure to answer an additional important research question. Registration number: ISRCTN00786323 (http://www.isrctn.com /). Abstract : Something to consider